Determinant Factors On Multidrug Resistant Tuberculosis (MDR TB) Control At RSUD dr. Zainoel Abidin Banda Aceh In 2018 - Nurlina, Nurlina; Usman, Said; Mudatsir, Mudatsir; Nurjannah, Nurjannah; Saputra, Irwan (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study used analytical survey method with cross sectional approach, primary and secondary data. There were 41 samples of MDR TB patients taken by using total sampling technique and analyzed with chi-square and followed by logistic regression. The results of the questionnaire on the management system on the MDR TB control is 70.7% which is good and from 41 samples of MDR TB patients, the related factors to the MDR TB control is comorbiditas (p value = 0.032) and the patients discipline in taking drug (p value = 0.001) , where as the unrelated factors is age and sex. From the results of the logistic regression test, the most related factor on the MDR TB control at RSUD dr. Zainoel Abidin is the patients’ discipline in taking medicine with p value of 0.006 and an OR value 11.50